2000
DOI: 10.1007/s002619910048
|View full text |Cite
|
Sign up to set email alerts
|

Paratesticular aggressive fibromatosis: CT findings

Abstract: Aggressive fibromatoses commonly originate from the musculoskeletal system, mesentery, and retroperitoneum. We report a case of aggressive fibromatosis arising from the spermatic cord. On helical computed tomography, the lesion appeared as a solid mass with well-defined borders in the scrotum and with infiltrative features in the retroperitoneum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…12 Unusual scrotal masses that have been reported include schwannoma, 13 simple epidermoid cyst, 14 ectopic pheochromocytoma, 15 and aggressive fibromatosis. 16 Lymphangiomas are very rare scrotal masses of which, to our knowledge, sonographic images have not been reported in the radiologic or sonographic literature.…”
Section: Discussionmentioning
confidence: 92%
“…12 Unusual scrotal masses that have been reported include schwannoma, 13 simple epidermoid cyst, 14 ectopic pheochromocytoma, 15 and aggressive fibromatosis. 16 Lymphangiomas are very rare scrotal masses of which, to our knowledge, sonographic images have not been reported in the radiologic or sonographic literature.…”
Section: Discussionmentioning
confidence: 92%
“…4 On imaging the mass extended into the retroperitoneum along the testicular artery. 4 This aggressive tumour invaded the bladder, sigmoid colon, left ureter and left external iliac vessels and was subsequently incompletely excised with margins at the left external iliac vessels and left ureter. 4 Similar to the case described in this review, the tumour was a solid and firm with a white surface; however, it was aggressive in nature.…”
Section: Discussionmentioning
confidence: 99%
“…Gluck et al [8] and Lai et al [9] reported 1 case each of AF arising primarily from the spermatic cord in 1987 and 1995 respectively. Sumi et al [10] described a case whose lesion originated from the spermatic cord and extended to the retroperitoneum through the internal inguinal ring. The mass invaded the bladder, the sigmoid colon, the left ureter, and the left external iliac vessels.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, only 3 cases of AF arising from the paratesticular structures have been described [8][9][10] ( table 1 ). Gluck et al [8] and Lai et al [9] reported 1 case each of AF arising primarily from the spermatic cord in 1987 and 1995 respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation